2022
DOI: 10.3390/technologies10010010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Air Stability of Perovskite Quantum Dots by Manganese Passivation

Abstract: Organic-inorganic perovskite quantum dots (PeQDs) have attracted attention due to their excellent optical properties, e.g., high photoluminescence quantum yields (PLQYs; >70%), a narrow full width at half maximum (FWHM; 25 nm or less), and color tunability adjusted by the halide components in an entire tunability (from 450 nm to 730 nm). On the other hand, PeQD stability against air, humidity, and thermal conditions has still not been enough, which disturbs their application. To overcome these issues, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…But, it has also certain disadvantages such as usage of polar solvents such as DMF degrade perovskite NCs and form defective perovskite NCs. [ 50 ] In this regard, Zhang et al had found that PbI 2 produces stable intermediates during the crystallization of MAPbI 3 NCs in presence of coordination solvents such as DMF, DMSO, and tetrahydrofuran, but it gets dissolved in noncoordinating solvents, such as acetonitrile and γ ‐butyrolactone. [ 51 ] Nature of solvents has vital effects on the formation of the crystal structure of the NCs.…”
Section: Synthesis Approaches For Preparation Of Hp Ncsmentioning
confidence: 99%
“…But, it has also certain disadvantages such as usage of polar solvents such as DMF degrade perovskite NCs and form defective perovskite NCs. [ 50 ] In this regard, Zhang et al had found that PbI 2 produces stable intermediates during the crystallization of MAPbI 3 NCs in presence of coordination solvents such as DMF, DMSO, and tetrahydrofuran, but it gets dissolved in noncoordinating solvents, such as acetonitrile and γ ‐butyrolactone. [ 51 ] Nature of solvents has vital effects on the formation of the crystal structure of the NCs.…”
Section: Synthesis Approaches For Preparation Of Hp Ncsmentioning
confidence: 99%
“…PeQD (Lead tri-halide (ABX3 A=Cs, MA (CH3NH2), and FA (NH2CHNH2), B=Pb, X=Cl, Br, and I) perovskite quantum dot) has greatly attracted attention as a light source to next generated optical materials due to its high PLQY (photoluminescence quantum yield) and high color purity attributed to narrow FWHM (full width at half maximum) [1][2][3][4][5] (Figure 1). Focusing on the emission wavelength, there are few reports on controlling the emission wavelength.…”
Section: Introductionmentioning
confidence: 99%